Prevalence of Hypertension in Semi-Urban area of Nepal - Koju, R; Manandhar, K; Gurung, R; Pant, P; Bedi, TRS (Nepalese Heart Journal, 2013)
Hypertension is one of the major cardiovascular problems in middle and low income countries. There are few studies conducted in Nepal which shows significant number of hypertensive population in suburban area. Systematic random sampling from voter lists of all the members more than 18 years of age of Dhulikhel Municipality was done. 796 among 1150 sampled population were interviewed and their blood pressure was measured twice using mercury sphygmomanometer in standard method in their home. The average blood pressure was taken for study. Hypertension was defined as systolic blood pressure ≥ 140 mmHg and/or diastolic blood pressure ≥ 90 mmHg, and/or on antihypertensive treatment. Total number of study population was 796. Among them 490 (61.6%) were female and 306 (38.4%) were male with age ranging from 18 years to 88 years (mean 48.41±17.38). Overall prevalence of hypertension was 28.9% (male 28.8%, female 29%). The prevalence was increasing with age (11.1% in <30 years to 44.8% in >70 years). According to JNC 7, 29.1% were in Pre-hypertensive group. This study shows that Hypertension is significant in suburban area of Nepal. Nepalese Heart Journal | Volume 7 | No.1 | November 2010 (special issue) | Page 35-39 DOI: http://dx.doi.org/10.3126/njh.v7i1.8500